Identification of a Locus Controlling Compound Raceme Inflorescence in Mungbean [Vigna radiata (L.) R. Wilczek] - Lee, Eunsoo; Yang, Xuefei; Ha, Jungmin; Kim, Moon Young; Park, Keum Yong; Lee, Suk-Ha (Frontiers in Genetics, 2021)
Mungbean (Vigna radiata (L.) R. Wilczek) produces a compound raceme inflorescence that branches into secondary inflorescences, which produce flowers. This architecture results in the less-domesticated traits of asynchronous pod maturity and multiple harvest times. This study identified the genetic factors responsible for the compound raceme of mungbean, providing a unique biological opportunity to improve simultaneous flowering. Using a recombinant inbred line (RIL) population derived from VC1973A, an elite cultivar with a compound raceme type, and IT208075, a natural mutant with a simple raceme type, a single locus that determined the inflorescence type was identified based on 1:1 segregation ratio in the F8 generation, and designated Comraceme. Linkage map analysis showed Comraceme was located on chromosome 4 within a marker interval spanning 520 kb and containing 64 genes. RILs carrying heterozygous fragments around Comraceme produced compound racemes, indicating this form was dominant to the simple raceme type. Quantitative trait loci related to plant architecture and inflorescence have been identified in genomic regions of soybean syntenic to Comraceme. In IT208075, 15 genes were present as distinct variants not observed in other landrace varieties or wild mungbean. These genes included Vradi04g00002481, a development-related gene encoding a B3 transcriptional factor. The upstream region of Vradi04g00002481 differed between lines producing the simple and compound types of raceme. Expression of Vradi04g00002481 was significantly lower at the early vegetative stage and higher at the early reproductive stage, in IT208075 than in VC1973A. Vradi04g00002481 was therefore likely to determine inflorescence type in mungbean. Although further study is required to determine the functional mechanism, this finding provides valuable genetic information for understanding the architecture of the compound raceme in mungbean.